SATIRICAL ELEMENTS IN SAID AHMAD'S WORK (British Journal of Global Ecology and Sustainable Development, 2023)
In this article, Said Ahmed, an Uzbek folk writer, is discussed in relation to the use of satire in his writing. In Said Ahmed's writing, satire plays a significant part.